Hearing the page: re-assessing the history and performance of the late medieval carol - MacKay, MA (2023)
Late medieval carols are an eclectic group of songs, ranging from pieces about good ale to solemn reflections on the Passion. They exist both in musically-notated books and in books without any notation at all. Despite this many scholars have neglected to examine these musically-notated works and their non-notated counterparts together. A gulf still exists between literary and musicological approaches to the form. This thesis addresses this lacuna by using an interdisciplinary literary, musicological, historical, and palaeographical approach to re-assess the history of the carol, from its development to its performance. In doing so, I re-write Richard Leighton Greene’s 1935 history of the carol, a history which has often gone unchallenged. By placing the carol in its international context and studying the contexts in which it was performed and the figures involved in its performance, I argue that there is far more nuance to the carol’s history than that provided by Greene. Having shown that the late medieval carol was a product of international exchange, collaboration, and travel, I propose that by examining the carol on the page and comparing musically-notated carol pieces to their non-notated counterparts we can begin to hear echoes of the carol’s performance and the wider performance culture of the late medieval period. This thesis therefore shows that the carol had a life that was more vibrant and complex than previously imagined. Indeed, if we attend to the carol corpus with an interdisciplinary and comparative focus we find that the manuscript page does not remain silent.